Pelatihan Pembuatan Makanan Lengkap yang Beragam, Bergizi Seimbang serta Aman (B2SA) bagi Penyuluh Umum Dinas Ketahanan Pangan dan Pertanian (DKPP) Kota Bandung - Sonny Sanjaya; Sara Rabasari; Surya Aditya Wahyono; Geri Supriyadi (Politeknik Piksi Ganesha Indonesia, 2022)
Cases of stunting in Indonesia are often found in low economic and social groups. Based on the Indonesian Toddler Nutrition Status Survey (SSGBI) in 2021, the stunting rate is around 24.4%, but the stunting rate has decreased compared to previous years. One of our strategies to reduce stunting is by holding a Complete Food Production Training that is Diverse, Nutritious, Balanced and Safe (B2SA). The target of this training is the General Extension Service for Food Security and Agriculture (DKPP) Bandung City. The target of this training is that participants are able to make a full set menu that is Diverse, Balanced and Safe (B2SA) which is expected to have an impact on reducing the birth of malnourished children.